Pengaruh Profitabilitas Terhadap Nilai Perusahaan dengan Pengungkapan CSR sebagai variabel Moderasi (Perusahaan yang tergabung di JII dan Indeks SRI-KEHATI periode 2016-2018) - Niswatin Chasanah; Sylva Alif Rusmita (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine and analyze the effect of profitability (ROA) on stock prices with corporate social responsibility (CSR) as a variable that moderates the two variables. The object of this research is companies incorporated in JII and SRI-KEHATI indexes that meet the test sample criteria during the period 2016 - 2018. This study uses a quantitative approach. Analysis of the data in this study used a moderation regression analysis (MRA). This study uses 20 samples for the JII index and 21 for the SRI-KEHATI index. Data obtained from the company's financial statements incorporated in JII and the SRI-KEHATI index for the period of 2016 - 2018 on the Indonesia Stock Exchange (IDX) website. The results showed that Return On Assets (ROA) had a significant effect on JII stock prices and SRI-KEHATI index stock prices. Furthermore, with CSR as a moderating variable showing the results of research with JII that is partially CSR disclosure shows a significant value which means CSR disclosure is able to moderate the relationship of ROA with JII stock prices. Overall (simultaneous) independent variables (ROA, CSR, ROA * CSR) significantly influence the stock price of JII. Furthermore, the results of research with the SRI-KEHATI index partially disclose CSR as a moderating variable showing a significant value. This means that CSR disclosure is not able to moderate the relationship of ROA with JII stock prices. while overall (simultaneous) independent variables (ROA, CSR, ROA * CSR) affect the stock price of the SRI-KEHATI index.Keywords: Profitability,StockPrice,ROA,CSR